Prediction of dysphagia after posterior fossa surgery - V. V. Podlepich; I. A. Savin; V. N. Shimanskiy (Вестник анестезиологии и реаниматологии, 2023)
Prediction of dysphagia after posterior fossa surgery (PFS) is a cornerstone on the well-timed extubation. Premature extubation is associated with the risk of aspiration, prolonged extubation leads to post-intubation dysphagia. PFSs are complicated by neurogenic dysphagia in 29–66% of cases. The use of classical methods for diagnosing dysphagia in the early postoperative period is difficult. Screening tests are characterized by low specificity.The objective was to develop an objective and accurate  clinical and electrophysiological model capable of predicting dysphagia.Materials and methods.  The study included  123 patients over 16 years old with extracerebral posterior fossa tumors. Somatosensory evoked potentials (SSEPs) were recorded  before the intervention and in the early postoperative period in a state of residual sedation  in intubated patients. Patients were divided into two groups by clinical assessment: without swallowing disorders and with dysphagia.Results. The model allows to identify 19 out of 20 patients with dysphagia and 77 out of 103 patients without dysphagia.Conclusion. The research showed the possibility of objective prediction of neurogenic dysphagia based on an accurate  digital method.